First documentation of Aspergillus welwitschiae in COVID-19- associated pulmonary aspergillosis in the Americas - Cocio, Tiago Alexandre (2025)
This study reports the first documented case of COVID-19-associated pulmonary aspergillosis (CAPA) caused by Aspergillus welwitschiae in the Americas, which occurred in a rural area of Sao Paulo State, Brazil. The case involves a 52-year-old woman with COVID-19, hypertension, and dyslipidemia, who was admitted following severe respiratory deterioration. Imaging tests revealed extensive pulmonary involvement, including nodular and cavitary lesions indicative of CAPA. Bronchoalveolar lavage (BAL) analysis identified Aspergillus spp. using morphological and molecular techniques, and sequencing of the benA gene confirmed the isolate as A. welwitschiae, closely related to the reference strain CBS 139.54. Matrixassisted laser desorption/ionization-time of flight mass spectrometry further validated this identification. Traditionally recognized as a plant pathogen, A. welwitschiae has recently been implicated in human diseases, such as otomycosis, and is increasingly detected in respiratory samples. However, its association with CAPA remains underreported globally, particularly in the Americas. This case highlights the critical importance of accurate fungal diagnosis, as overlapping morphological features among Aspergillus species can hinder clinical management. The identification of A. welwitschiae in this context raises concerns about its potential as an emerging pathogen in agricultural regions, where environmental exposure may drive its epidemiological relevance. Given the growing recognition of A. welwitschiae as a CAPA agent, this report underscores its importance in the epidemiology of the disease and its potential role in regions with high agricultural activity. Accurate identification is essential for guiding targeted interventions and addressing the public health risks posed by this emerging fungal threat toCOVID-19 patients.